Mortality in patients with hematological malignancies, febrile neutropenia, and septic shock - Beda Islas-Muñoz; Patricia Volkow-Fernández; Jorge Silva-Zamora; Ana Ramírez-Ibarguen; Patricia Cornejo-Juárez (Journal of Infection in Developing Countries)
Introduction: Patients with severe neutropenia who develop septic shock (SS) have high mortality. This study aimed to evaluate the risk factors and mortality of SS in patients with HM and febrile neutropenia.